A Model Intervention for Girls With Disruptive Behaviour Disorders: The Earlscourt Girls Connection - Walsh, M. M.; Pepler, D. J.; Levene, K. S. (Canadian Journal of Counselling and Psychotherapy, 2007)
In 1996, the Earlscourt Girls Connection (EGC), a gender-specific programme for young girls with conduct problems, was initiated at Earlscourt Child and Family Centre, a children's mental health agency. As part of an evaluation of the EGC, analyses of behavioural change according to primary caregivers' ratings were conducted comparing admission scores with 6-month (N = 72) and 12-month (N = 58) follow-up. At follow-up, the girls were rated as lower on the total score for externalizing behaviours and on several internalizing and externalizing subscales of the Standardized Client Information Systems (SCIS). The girls were also rated as having increased prosocial behaviours. Differences in scores on externalizing behaviours ranged from small to medium effects, and a large effect for the improvement in social relations. Variability in intervention responsiveness provided direction for future development of this multifaceted treatment programme for aggressive girls.